The Impact of Environmental Factors on Families with Disabilities as an Object of Structural Modeling - PRITVOROVA, Tatyana; TEMIRBAYEVA, Dinara; GORDEYEVA, Yelena; KUTTYBAEVA, Nurgul; SPANOVA, Bakyt (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).02, 2022)
This article examines the socio-economic situation of families with children with disabilities, who are considered vulnerable social groups in global social policy. The purpose of the paper is to assess the set of constraints faced by families with children with disabilities in Kazakhstan and the factors, including environmental factors, that have a significant impact on them. The authors use a sociological survey of respondents in five regions of Kazakhstan and subsequently process the results using statistical methods. The survey is based on a methodological approach based on the identification of four types of constraints: direct costs, indirect losses/costs, assessment of the ability to find a job, and assessment of the ability to maintain a parent's health. The authors conduct structural modeling using the PLS-PM model, in which four types of constraints are set as dependent variables. The model allowed eight hypotheses to be confirmed, of which six identify significant factors and the other two reflect the relationships among the dependent variables in the model.